P 3 Cerebellar gray matter volume decrease is associated with epileptic seizures in multiple sclerosis. Issue 10 (October 2017) - Grothe, M.; Süße, M.; von Podewils, F.; Langner, S.; Lotze, M.; Domin, M.
Abstract : Background: Prevalence rates of epileptic seizures are three times higher in patients with multiple sclerosis (MS) compared to healthy controls (van Munster et al., 2015 ). There is some evidence of gray matter (GM) as well as white matter (WM) lesions associated with epilepsy in MS (van Munster et al., 2015 ). Here, we compared regional GM volume decrease using voxel based morphometry (VBM) to compare MS patients with and without epilepsy. Methods: MRI images of 30 MS patients (15 with, 15 without epilepsy, matched due to disease duration, disease course, EDSS and age) were analyzed using voxel based morphometry. Second level analysis was done comparing regional GM volume in MS patients without compared to with epileptic seizures. Results: MS-patients with epilepsy had regional GM volume decrease in the cerebellum compared to MS patients without epilepsy, mainly in the posterior lobe. Neither cerebral or deep GM structures revealed significant regional GM volume decrease. Discussion: There is some evidence of hippocampal GM pathology associated with epilepsy (Nicholas et al., 2016 ). In contrast, our VBM analyses did not reveal any association to cortical or subcortical GM volume decrease. Against our expectations, we found significant cerebellar GM volume decrease in the patients with, compared to without epileptic seizures. Interestingly, there is some evidence of cerebellar lesions generating seizures (Foit et al., 2016 ), cerebellar abnormalities in idiopathic generalized epilepsy (Li et al., 2010 ) as well as a cerebellar mediated, inhibitory effect on hippocampal seizures (Krook-Magnuson et al., 2014 ). Our data has to be confirmed in larger samples, but at least are indicating a possible role of the cerebellum in MS patients with epilepsy.